Seismic Demand Prediction in Laminated Bamboo Frame Structures: A Comparative Study of Intensity Measures for Performance-Based Design - Yantai Zhang; Jingpu Zhang; Yujie Gu; Jinglong Zhang; Kaiqi Zheng (Buildings)
Engineered laminated bamboo frame structures have seen notable advancements in China, driven by their potential in sustainable construction. However, accurately predicting their seismic performance remains a pivotal challenge. Structural and non-structural damage caused by earthquakes can severely compromise building operability, lead to substantial economic losses, and disrupt safe evacuation processes, collectively exacerbating disaster impacts. To address this, three laminated bamboo frame models (3-, 4-, and 5-story) were developed, integrating energy-dissipating T-shaped steel plate beam–column connections. Two engineering demand parameters—peak inter-story drift ratio (PIDR) and peak floor acceleration (PFA)—were selected to quantify seismic responses under near-field and far-field ground motions. The study systematically evaluates suitable intensity measures for these parameters, emphasizing efficiency and sufficiency criteria. Regarding efficiency, the applicable intensity measures for PFA differ from those for PIDR. The measures for PFA tend to focus more on acceleration amplitude-related measures such as peak ground accelerations (PGA), sustained maximum acceleration (SMA), effective design acceleration (EDA), and A95 (the acceleration at 95% Arias intensity), while the measures for PIDR are primarily based on spectral acceleration-related measures such as Sa(T1) (spectral acceleration at fundamental period), etc. Concerning sufficiency, significant differences exist in the applicable measures for PFA and PIDR, and they are greatly influenced by ground motion characteristics.